PERLINDUNGAN HUKUM TERHADAP SAKSI PELAKU (JUSTICE COLLABORATOR) DALAM TINDAK PIDANA KORUPSI - Irwan Effendi; Ida Ayu Eka Putri Yuliandari (Faculty of Law, Mahasaraswati University, Denpasar, 2024)
Guarantees for the implementation of certain rights regulated in article PSK Law there is no explanation of how to implement the regulations and provide the rights listed and contained in article 5, resulting in witnesses unwilling and unwilling to give statements before the court. Formulation of the problem (1) how is the legal protection for the witnesses of the perpetrators (Justice Collaborator) in corruption? (2) What is the criminal sanction given to the witnesses of the perpetrators (Justice Collaborator) against criminal acts of corruption? In writing this thesis, the legal research used is normative legal research. Using analysis of legal interpretation in order to answer the problems raised. As for the legal protection for witnesses of the Justice Collaborator against corruption, it is deemed necessary, considering that to guarantee the security of the perpetrators themselves while giving their testimony and testimony in court. Criminal sanctions are given to witnesses of the Justice Collaborator against corruption, namely the Judge may consider the conviction of a criminal conviction for conditional probation and / or imprisonment in the form of the lightest imprisonment among other defendants found guilty, as well as providing special treatment for witnesses of the offender cooperate and get special handling also in detention, file inspection and security while giving testimony. Protection for witnesses of perpetrators can be seen as very necessary, given to guarantee the security of the perpetrators themselves while providing information and testimony in court. Judges may consider convicting them with consideration of imposing special conditional probation penalties and / or imposing penalties in the form of the lightest imprisonment among other defendants who are proven guilty and provide special treatment.